ChemInform Abstract: A Concise Synthesis of Asymmetrically 4, 5‐Disubstituted 9, 9‐Dimethyl‐9H‐xanthenes. Issue 24 (June 2015) - Matsubara, Ryosuke; Koide, Miki; Shin, Yong‐Soon; Shimada, Toshiyuki; Hayashi, Masahiko
Abstract: The selective metal‐halogen exchange of dibromodimethylxanthenes delivers a monolithiated species which is transmetalated to zinc organometallics; subsequent coupling with diverse reagents leads to formation of monofunctionalized xanthenes.